Relationship of Remuneration Policy to the Performance of Specialist Doctors in the Kramat Jati Regional General Hospital in 2022 - Suranta, Roy Michael; Gani, Ascobat; Bachtiar, Adang (UI Scholars Hub, 2024)
The number and types of hospitals in Jakarta are constantly increasing, causing competition for customers or patients. Hospitals owned by the DKI Jakarta provincial government face challenges in providing specialist doctor services with the best performance for the community, this is closely related to the rewards offered to specialist doctors. One of the regional government's efforts to improve the performance of specialist doctors is by issuing regulations on remuneration for hospitals. This research aims to determine the relationship between remuneration policy and the performance of specialist doctors at Kramat Jati Regional Hospital. The research was conducted using a case study method with a qualitative approach. The research was conducted on 11 specialist doctors using questionnaires and in-depth interviews with informants. The results of the study found that the implementation of the remuneration policy at Kramat Jati Regional Hospital increased the average income of specialist doctors by 42.9% of the income of specialist doctors before the implementation of remuneration. This study also found that the implementation of remuneration policies at Kramat Jati Regional Hospital was related to the quantity performance of specialist doctors.